ETHICAL CONFLICTS EXPERIENCED BY IRANIAN EFL TEACHERS IN THE CLASSROOM CONTEXT - Zahra Alimorad (TEFLIN, 2014)
Â Recently, EFL teachersâ ethical conflicts in the situated classroom context have got paramount importance. This paper presents findings from an empirical study of ethical conflicts Iranian EFL teachers encounter while engaged in classroom assessment. Critical incidents generated by 49 practicing teachers revealed that a majority of reported conflicts were related to Do No Harm principle. Most of the conflicts they encountered involved basic values as one of the conflicting elements while two new conflicting elements emerged in the specific context of this study. It was concluded that Iranian educational policy might need to be changed to mitigate some of these conflicts.Â